Increasing women's effective participation and leadership in decision-making: Guidance for voluntary sustainability systems - Morgan, Miranda (2023)
Voluntary Sustainability Systems (VSS) are varied in their commitments, actions and performances on gender equality. But as more VSS seek to address gender inequalities in agri-food value chains, the timing is ripe to reflect on existing evidence to inform future strategies. A recent evidence review sought to understand if and how VSS can support women’s full and effective participation and leadership in decision-making in agri-food value chains. It found that while VSS have led to some measurable benefits on certain aspects of women’s empowerment (especially on economic inclusion and higher incomes) for some women, VSS can do more to significantly increase women’s participation, representation and leadership in decision-making.